Kajian Kondisi Keberadaan Anoa Dataran Rendah dengan Anoa Pegunungan di Pulau Sulawesi Ditinjau dari Jenis Pakannya - Daffa Azalia; Intan Rachmawati; Ade Suryanda (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Anoa is an endemic animal on Sulawesi island which is threatened with extinction, both lowland anoa (Bubalus depressicornis) and mountain anoa (Bubalus quarlesi) which share the status of Endangered. The aim of this study is to determine the condition of lowland anoa and mountain anoa on the Sulawesi island in terms of the type of feed. Methods: This research was accomplished using literature review techniques. Results: The outcome of this study showed a represent that lowland anoa in terms of feed type has an endangered status, as well as mountain anoa in terms of feed type, which is endangered. The status of the existence of lowland anoa and mountain anoa, both from the type of feed and the IUCN conservation organization, is equally threatened with extinction. The same condition and conservation status is obtained by the result because the two different anoas that lives in different habitats are able to adjust their own feed according to where the animals are. Conclusions: Although it has no bearing on anoa condition and conservation status, it is expected that the national park and captivity of anoa on Sulawesi Island can better sort food for lowland anoa and mountain anoa to support their physiological functions for their existence.